MOTIVATIONAL IMPACTS OF ADVERTISING ON ONLINE SHOPPING FOR AIRLINE TICKETS ( March 2017) - De Guzman, Jor-el A.; Gomez, Kathleen Grace, Mas, Katrisha Celine M.; and Ramos, Cristine Joyce B. 4 0 16; 5
u
Thesis (Undergraduate) Pamantasan ng Lungsod ng Maynila, 2017.;Bachelor of Science in Travel and Tourism Management.;COLLEGE OF BUSINESS AND MANAGEMENT- Institute of Tourism and Hospitality Management.
Keywords: 2 -- 0; 6; 20; 20; 2